Enhancing Performance: The Role of Organizational Culture, Commitment, and Support in Indonesian Paper Industry - Dudija, Nidya; Naibaho, Sartika; Wibowo, Satrio Budi (Jurnal Psikologi, 2024)
Human resources play an important role in the successful achievement of performance. Employee performance is the result of the work achieved by employees in a company. This study aims to investigate the impact of organizational culture, organizational commitment, and perceived organizational support on employee performance at a paper manufacturing plant. The descriptive data and SEM were analyzed using The Jeffreys’s Amazing Statistics Program (JASP) method. Data were collected from 107 respondents who participated in paper manufacturing plants (52 males (48.6%), 55 females (51.4%); MageMage= 38, SD = 8.4). The results showed that (1) organizational culture has a significant effect on employee performance (β = 0,533, p 0,05). (3) Perceived organizational support has no significant effect on employee performance (β = 0,039, p > 0.05). In this study, organizational commitment and perceived organizational support did not influence employee performance. Among employees, expectations for increasing organizational commitment and perceptions of organizational support for improving employee performance are still not high enough. The findings of this study highlight that organizational culture has the strongest influence compared to organizational commitment and perceived organizational support on employee performance. To improve employee performance, organizations can internalize cultural values through socialization activities, corporate culture training, and cultural rituals so that employee work behavior will develop, contributing to improved performance in the organization.